To the honorable General Assembly of the state of Rhode Island & Providence Plantations, to be holden at Providence in said state, on the second Monday of January in the year 1832
January 9, 1832 Objections of the Narragansett Tribe to the General Assembly regarding Dan King's report in January 1831 concerning the conditions of their tribe. This remonstrance objected to the proposed changes of the laws, which included the appointment of an overseer and treasurer. The tribe also stated that their four thousand acres of land (1/5 was swamp and undivided) was needed for a variety of purposes, noting that white people "got away" with the best land. The tribe also indicated various examples of proof that they were not "savages," including the number of churches and meeting houses.